2010
DOI: 10.1051/vetres/2010034
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of mucosal associated invariant T (MAIT) cells and the MR1 restriction element in ruminants, and abundance of MAIT cells in spleen

Abstract: MHC-related protein 1 (MR1) is a highly conserved MHC class I-like molecule. Human and murine mucosal associated invariant T (MAIT) cells are restricted by MR1 and express an invariant T cell receptor. Even though MR1 protein expression on the cell surface has not been demonstrated in vivo or ex vivo, it is assumed that MR1 presents a bacterial antigen from the intestinal lumen to MAIT cells because MAIT cells are present in the lamina propria and their expansion is dependent on the presence of intestinal micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
59
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 22 publications
6
59
1
Order By: Relevance
“…The almostinvariant TCRa chain of MAIT cells is evolutionarily conserved in mammals 14,19 and results from a single Va-Ja rearrangement with a defined CDR3a length. In humans, some variation in the composition of the junction exists, suggesting a selective pressure operating at the protein level 14 .…”
mentioning
confidence: 99%
“…The almostinvariant TCRa chain of MAIT cells is evolutionarily conserved in mammals 14,19 and results from a single Va-Ja rearrangement with a defined CDR3a length. In humans, some variation in the composition of the junction exists, suggesting a selective pressure operating at the protein level 14 .…”
mentioning
confidence: 99%
“…The MAIT TCR ␣-chain contains a complementarity-determining region (CDR) 3 loop of constant length with two variable amino acids in the V-J junction (4) located at the base of this loop (10,11). MAIT cells are evolutionarily conserved in mammals with the canonical TCR ␣-chain composed of homologous TRAV and TRAJ elements also found in mice, cattle (5) and sheep (12). TRAV1-2 is not exclusive to MAIT cells, with some MHC-Irestricted T cells (13,14) and CD1b-restricted germline-encoded, mycolyl lipid-reactive (GEM) T cells also using this TRAV gene segment (15).…”
Section: Mait Cellsmentioning
confidence: 99%
“…In contrast, mutagenesis experiments associated with structural studies identified crucial residues in the CDRs of the TCRa-chain that are required for Ag recognition by MAIT cells, regardless of Vb2 Jb usage (12). These residues are conserved in mammals (13,14). Although MAIT cell TCRs use preferential Vb segments, mutagenesis of individual residues within the CDRb regions indicates that the TCRb-chain of the MAIT cell TCRs did not play an important role in Ag reactivity, consistent with the lack of TCRb constraints (12,15).…”
mentioning
confidence: 93%